7D.09: REDUCED VIT D AND ELEVATED URICEMIA INDUCE CAPILLARY RAREFACTION BEFORE MACROVASCULAR DAMAGE IN PATIENTS WITH METABOLIC SYNDROME AT THE VERY EARLY STAGES OF HYPERTENSION. (June 2015) - Nazzaro, P.; Schirosi, G.; De Benedittis, L.; Mezzapesa, D.; Federico, F.
Abstract : Objective: Reduced (L) Vit D (D) and high (H) uric acid (U) levels have been associate with increased cardiovascular risk. Aim of the study was to highlight their association with the subclinical vascular damage in untreated recently diagnosed very mild hypertensives with a similar number of metabolic syndrome factors (nATPIII). Design and method: By medical visit and identification of the metabolic syndrome factors, 238 very mild hypertensives (136 ± 15/84 ± 9 mmHg), 62 controls with normal (N) D and U, 96 with LD, 40 with HU and 40 with both the conditions (LDHU) with similar metabolic assessment, underwent measures of carotid-femoral pulse wave velocity (PWV), ankle-brachial index (ABI), carotid intima-media thickness (IMT), as indices of functional and structural arterial damage, and videocapillaroscopy of the middle and distal phalangeal skin of the 2nd, 3rd and 4th finger of the non-dominant hand during baseline (CAP) and venous congestion (CVC) obtaining capillary recruitment (REC) as indices of functional and structural microcirculatory damage. Results: Patients showed a similar hypertensive state during the medical visit and ABPM but different capillary indices. (m ± s:d.*:p<.05, **:p < .01, ***:p < .001 vs NDNU; °:p < .05, °°:p < .01, °°°:p < .001 vs LDNU;^p < .05, ^^:p < .01, ^^^:p < .001 vs NDHU). Figure. No caption available. Pearson analysis showed the association between Vit D and CVC (.440*) and REC (.335***) in LDNU and with CVC (631***) and REC (.666*) in LDHU as well as between U and CAP (-.470*) in NDHU and (-606*) in LDHU. Conclusions: The results suggest that, in very mild hypertensives with metabolic syndrome, reduced Vit D is associate to structural microvascular damage before the onset of structural or functional macrovascular impairment. Hyperuricemia show a lower microcirculatory damage but this is amplified in patients with both the disorders (LDHU),